Intra- and extraneuronal changes of immunofluorescence staining for TNF-alpha and TNFR1 in the dorsal root ganglia of rat peripheral neuropathic pain models - Dubový, P; Jancálek, R; Klusáková, I; Svízenská, I; Pejchalová, K (Cellular and molecular neurobiology, 2006)
1. Several lines of evidence suggest that cytokines and their receptors are initiators of changes in the activity of dorsal root ganglia (DRG) neurons, but their cellular distribution is still very limited or controversial. Therefore, the goal of present study was to investigate immunohistochemical distribution of TNF-alpha and TNF receptor-1 (TNFR1) proteins in the rat DRG following three types of nerve injury. 2. The unilateral sciatic and spinal nerve ligation as well as the sciatic nerve transection were used to induce changes in the distribution of TNF-alpha and TNFR1 proteins. The TNF-alpha and TNFR1 immunofluorescence was assessed in the L4-L5 DRG affected by nerve injury for 1 and 2 weeks, and compared with the contralateral ones and those removed from naive or sham-operated rats. A part of the sections was incubated for simultaneous immunostaining for TNF-alpha and ED-1. The immunofluorescence brightness was measured by image analysis system (LUCIA-G v4.21) to quantify immunostaining for TNF-alpha and TNFR1 in the naive, ipsi- and contralateral DRG following nerve injury. 3. The ipsilateral L4-L5 DRG and their contralateral counterparts of the rats operated for nerve injury displayed an increased immunofluorescence (IF) for TNF-alpha and TNFR1 when compared with DRG harvested from naive or sham-operated rats. The TNFalpha IF was increased bilaterally in the satellite glial cells (SGC) and contralaterally in the neuronal nuclei following sciatic and spinal nerve ligature. The neuronal bodies and their SGC exhibited bilaterally enhanced IF for TNF-alpha after sciatic nerve transection for 1 and 2 weeks. In addition, the affected DRG were invaded by ED-1 positive macrophages which displayed simultaneously TNFalpha IF. The ED-1 positive macrophages were frequently located near the neuronal bodies to occupy a position of the satellites. 4. The sciatic and spinal nerve ligature resulted in an increased TNFR1 IF in the neuronal bodies of both ipsi- and contralateral DRG. The sciatic nerve ligature for 1 week induced a rise in TNFR1 IF in the contralateral DRG neurons and their SGC to a higher level than in the ipsilateral ones. In contrast, the sciatic nerve ligature for 2 weeks caused a similar increase of TNFR1 IF in the neurons and their SGC of both ipsi- and contralateral DRG. The spinal nerve ligature or sciatic nerve transection resulted in an increased TNFR1 IF located at the surface of the ipsilateral DRG neurons, but dispersed IF in the contralateral ones. In addition, the SGC of the contralateral in contrast to ipsilateral DRG displayed a higher TNFR1 IF. 5. Our results suggest more sources of TNF-alpha protein in the ipsilateral and contralateral DRG following unilateral nerve injury including macrophages, SGC and primary sensory neurons. In addition, the SGC and macrophages, which became to be satellites, are well positioned to regulate activity of the DRG neurons by production of TNF-alpha molecules. Moreover, the different cellular distribution of TNFR1 in the ipsi- and contralateral DRG may reflect different pathways by which TNF-alpha effect on the primary sensory neurons can be mediated following nerve injury.
Keywords: TNF-alfa; Fluorescent Antibody Technique; ženské pohlaví; Pain; neurony; Receptors, Tumor Necrosis Factor, Type I; Rats; potkani Wistar; Animals; Neurons; receptory TNF - typ I; Peripheral Nervous System Diseases; Rats, Wistar; Disease Models, Animal; zvířata; bolest; spinální ganglia; modely nemocí na zvířatech; Ganglia, Spinal; Tumor Necrosis Factor-alpha; krysa rodu Rattus; nemoci periferního nervového systému; Female; fluorescenční protilátková technika